1990
DOI: 10.1159/000310124
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Measurement of Human Lens Opacities Using the Lens Opacity Meter

Abstract: Lens opacity was quantified in 85 cataractous patients, using a new instrument: the lens opacity meter 701 (LOM; Interzeag, Schlieren, Switzerland). Cataracts were classified as nuclear, cortical, subcapsular and mixed forms. Sensitivity, specificity and reproducibility of the results were evaluated by statistical analysis. Visual acuity was correlated with LOM values in patients with nuclear and mixed cataracts. Moreover, the instrument gave a good degree of reproducibility only in patients who presented thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…As the lens opacities in this series were mostly nuclear, especially early nuclear, and mixed, LOM seemed to be a suitable instrument for this study, although it measures opacities in the central portion of the lens only, not in the whole lens. LOM does not measure posterior subcapsular cataract (Costagliola et al 1990;Stoltenberg et al 1989); that was evaluated clinically.…”
mentioning
confidence: 99%
“…As the lens opacities in this series were mostly nuclear, especially early nuclear, and mixed, LOM seemed to be a suitable instrument for this study, although it measures opacities in the central portion of the lens only, not in the whole lens. LOM does not measure posterior subcapsular cataract (Costagliola et al 1990;Stoltenberg et al 1989); that was evaluated clinically.…”
mentioning
confidence: 99%
“…Studies on cataract patients have shown that the reproducibility of this method is good for nuclear and mixed cataracts and poor for cortical and posterior subcapsular cataracts [6]. For merely clinical purposes a non-dilated 4 mm pupil is satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the follow-up of glaucomatous patients the appearance of lens opacities does not invali date the visual field interpretation. We have restricted the study only to cataracts affecting the central area of the lens because of the limi tations caused by the use of the LOM to quan tify lens opacities [6]. Obviously, further stud ies designed according to the type of cataract and performed with instruments able to quan tify each type of lens opacity are needed to ascertain whether other forms of cataract also validate the visual field interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…We have studied the lens opacity meter (LOM), an instru ment based on the concept of the measure ment of stray light produced by the lens [4], In our previous investigations we have ver ified the ability of this instrument to quantify the light scattering that occurs both with lens aging in healthy subjects [5] and with the presence of lens opacities in cataractous pa tients [6].…”
Section: Introductionmentioning
confidence: 99%